Accelerating Uterine Involution: The Role of Postpartum Exercise in Primary Care Settings - Nelli, Ermeida (Open Access Indonesian Journal of Medical Reviews, 2024)
Uterine involution, the process of the uterus returning to its pre-pregnancy state, is a critical physiological event in the postpartum period. Suboptimal involution can lead to complications such as postpartum hemorrhage and prolonged lochia. Postpartum exercise has been suggested to promote uterine involution, but its efficacy in primary care settings remains under-explored. This study aimed to investigate the impact of a structured postpartum exercise program on uterine involution in women receiving care in primary care clinics. A randomized controlled trial was conducted involving postpartum women attending primary care clinics. Participants were randomly assigned to either an intervention group, receiving a structured postpartum exercise program, or a control group, receiving standard postpartum care. The primary outcome was the rate of uterine involution, assessed through serial measurements of fundal height. Secondary outcomes included duration of lochia, postpartum pain, and maternal quality of life. The study enrolled 120 women (60 per group). The intervention group demonstrated a significantly faster rate of uterine involution compared to the control group (p < 0.05). Additionally, the intervention group reported a shorter duration of lochia and improved quality of life scores. No significant differences were observed in postpartum pain between the groups. A structured postpartum exercise program implemented in primary care settings can effectively accelerate uterine involution and improve maternal well-being. These findings underscore the importance of integrating postpartum exercise into routine primary care for postpartum women.